PROPHET AS LOGOS: A Perennial Philosophy Perspective on the Metaphysical Roots of Prophethood - Subhi, Mohammad; Hakim, Lukman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The article studies the metaphysical roots of prophethood from the perspective of perennial philosophy. The main problem discussed here is what is meant by “prophet as logos”. The discussion is around the principles of metaphysic which is typical of perennial philosophy. Employing library research included in qualitative methodology, the study delves into the key texts of perennial philosophers about prophethood. The primary data were taken and interpreted from the masterpieces of the renowned perennial philosophers: Frithjof Schuon, Seyyed Hossein Nasr, and William Stoddart. The secondary data were from relevant literature from books and articles. The study reveals that prophet is a reflection of the Absolute which is the seed of the universe (cosmological function), the saver (prophetic function), and the guide (initiative function) of humans. In Islam system, the “prophet as logos” is represented by Muhammad. Physically, he is just a man delegated by Allah, meanwhile spiritually, Muhammad is the “logos”.